SOCIAL MEDIA AND STUDENTS' ACADEMIC PERFORMANCE: A Case Study of Students Pursuing Business Administration at Higher Education Institution in Phnom Penh, Cambodia - Bunteng, Long (jfpublisher, 2023)
The purpose of this research is to examine the effect of social media on students' academic performance. The case study is based on the academic performance of students majoring in business administration at a higher education institution in Phnom Penh, Cambodia. A conceptual framework was developed from previous research which includes social media information, social media innovation, social media entertainment, social media knowledge generation, and student performance. Quantitative methods were used to distribute questionnaires to 376 respondents. A multistage sampling technique was conducted by nonprobability sampling, using judgmental sampling to select university students, quota sampling to calculate the sample size, and convenience sampling to distribute the questionnaire online, using several popular social networks. Before collecting data, the Index of Item-Objective Congruence (IOC) was used to validate the constructs. Factor loadings and Cronbach's alpha were tested for reliability, using 50 respondents as a pilot study, single and multiple linear regressions were applied to test hypotheses, and correlation matrices were used to identify variable relationships. The results indicated that social media information, social media innovation, and social media entertainment have a strong effect on social media knowledge creation. In addition, social media knowledge creation has a strong impact on student performance.